THE EFFECTS OF ISLAMIC ETHICAL IDENTITY INDEX ON FINANCIAL PEPRFORMANCE - Utami, Indah Setia; Suyono, Eko; Pramuka, Bambang Agus (Indonesian Journal of Islamic Business and Economics (IJIBE), 2019)
This study examines,firstly, the influence of Islamic Ethical Identity disclosure on Return on Asset, Return on Equity, and Economic Value Added of Islamic Bank in Indonesia, Malaysia, and Gulf Cooperation Council (GCC) Countries, and secondly,this study also examines the differences of Islamic Ethical Identity disclosure and Financial Performance between Islamic Bank in Indonesia-Malaysia and GCC Countries. This study uses panel data from 2008-2013 which published in website of each Islamic Bank selected as a sample in this study.The result of regression shows that the disclosure of Islamic Ethical Identity hasa signifficant effect on ROA, ROE, and EVA. Meanwhile, the result of independent T-test shows that there is no differences on Islamic Ethical Identity Disclosure and Financial Performance between Islamic Bank in Indonesia-Malaysia and GCC Countries.